Clinical and Epidemiological Characteristics of COVID-19 in Persons Living with HIV Complicated by Tuberculosis - I. B. Lebedeva; O. D. Borodkina; T. Ye. Bondarenko; Ye. B. Brusina (Эпидемиология и вакцинопрофилактика)
Relevance. At present, three infections – HIV infection, tuberculosis, and COVID-19 - are spreading simultaneously in the world. Of great practical importance is the assessment of clinical and epidemiological features of COVID-19 in HIV-infected patients with tuberculosis, COVID-19. Aim. To study the risk of COVID-19 disease and identify clinical and epidemiological features in and population of patients with HIV infection complicated by tuberculosis in comparison with patients with HIV infection and the population without these diseases.Materials and methods. Since 13.03.2020 by 31.12.2021 in the Kemerovo Region-Kuzbass, a continuous prospective analytical epidemiological study of the case-control type was performed. Of those with COVID-19, two observation groups were formed: group I (HIV +), group II (HIV/TB) and comparison group III (persons without either HIV or tuberculosis). All patients underwent: determination of SARS-CoV-2 RNA, standard examination methods in accordance with the temporary methodological recommendations «Prevention, diagnosis and treatment of a new coronavirus infection (COVID-19)», relevant at the time of treatment.Results. The incidence of COVID-19 among patients with HIV infection complicated by tuberculosis exceeded the incidence of COVID-19 among HIV-infected by 14%. There were no gender differences between patients I (HIV +) and II (HIV/TB) groups. In the comparison group, the incidence of COVID-19 was 1.26 times higher in women compared to men. COVID-19 disease in patients with co-infection (HIV/TB) was predominantly mild. Viral pneumonia developed 1.86 times less often, oxygenotherapy was required only in 18.75% of cases, which is 2.5 times lower than in group I (HIV +) and 2.47 times less than in the comparison group (III). In labeled pairs, clinical symptoms of COVID-19 in all groups occurred with the same frequency. Metabolic disorders were evident in all groups. Co-infected patients (HIV/TB) had higher levels of D-dimer, ESR, total bilirubin.Conclusion. Active tuberculosis in HIV-infected people is a factor that increases the risk of COVID-19 disease without affecting the severity of the infectious process.